Does Self-Licensing Benefit Self-Regulation Over Time? An Ecological Momentary Assessment Study of Food Temptations. (June 2018) - Prinsen, Sosja; Evers, Catharine; Wijngaards, Leoniek; van Vliet, Renée; de Ridder, Denise
Self-licensing, employing reasons to justify indulgence, may help resolve the conflict between immediate temptations and long-term goals in favor of the former. It was hypothesized that this conflict-resolving potential of self-licensing may benefit self-regulation over time. With a momentary assessment design, we examined how self-licensing affects self-regulatory ability and the capacity to deal with subsequent self-regulatory conflicts. One hundred thirty-six female participants filled out surveys eight times per day for one week. Food temptation strength, conflict, resistance, and enactment were assessed, as well as license opportunity and perceived self-regulatory ability. When self-licensing opportunity was high (vs. low), a weaker association between temptation strength and conflict was observed. High license opportunity was associated with higher perceived self-regulatory ability for instances of low degrees of temptation enactment and predicted better handling of subsequent conflict after high degrees of prior temptation enactment. These results suggest that self-licensing can support self-regulation after initial failure.